2022
DOI: 10.3389/fpls.2022.863211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Decision Support Tools for Precision Nitrogen Management on Creeping Bentgrass Putting Greens

Abstract: Nitrogen (N) is the most limiting nutrient for turfgrass growth. Few tools or soil tests exist to help managers guide N fertilizer decisions. Turf growth prediction models have the potential to be useful, but the lone turfgrass growth prediction model only takes into account temperature, limiting its accuracy. This study investigated the ability of a machine learning (ML)-based turf growth model using the random forest (RF) algorithm (ML-RF model) to improve creeping bentgrass (Agrostis stolonifera) putting gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…Thus N max , as estimated by Woods (2013) and Zhou and Soldat (2022), is an overestimate of the N required on golf courses from this study. This study finds that N max values needed to predict golf course N use rates are lower than currently published N max values.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…Thus N max , as estimated by Woods (2013) and Zhou and Soldat (2022), is an overestimate of the N required on golf courses from this study. This study finds that N max values needed to predict golf course N use rates are lower than currently published N max values.…”
Section: Discussioncontrasting
confidence: 61%
“…The implicit assumption in this method of estimating N max is that all N leaving the system is leaving through clippings, and that replacing this N will lead to a balanced N budget. Zhou and Soldat (2022) found that the amount of N leaving a research green through clippings loss in the 2019 growing season was 230 kg N ha −1 , on a plot of creeping bentgrass that was fertilized with 120 kg N ha −1 which was the highest N rate in the study. This resulted in an N max value of 39 kg ha −1 month −1 , within the range of the values used by Woods (2013).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations